Targeting the Microtubule-Network Rescues CTL Killing Efficiency in Dense 3D Matrices - Zhao, Renping; Zhou, Xiangda; Khan, Essak S.; Alansary, Dalia; Friedmann, Kim S.; Yang, Wenjuan; Schwarz, Eva C.; del Campo, Aránzazu; Hoth, Markus; Qu, Bin (Frontiers in Immunology, 2021)
Efficacy of CTL-based immunotherapy is still unsatisfactory against solid tumors, which are frequently characterized by condensed extracellular matrix. Here, using a unique 3D killing assay, we identify that the killing efficiency of primary human CTLs is substantially impaired in dense collagen matrices. Although the expression of cytotoxic proteins in CTLs remained intact in dense collagen, CTL motility was largely compromised. Using light-sheet microscopy, we found that persistence and velocity of CTL migration was influenced by the stiffness and porosity of the 3D matrix. Notably, 3D CTL velocity was strongly correlated with their nuclear deformability, which was enhanced by disruption of the microtubule network especially in dense matrices. Concomitantly, CTL migration, search efficiency, and cytotoxicity in dense collagen were significantly increased in microtubule-perturbed CTLs. In addition, the chemotherapeutically used microtubule inhibitor vinblastine drastically enhanced CTL killing efficiency in dense collagen. Together, our findings suggest targeting the microtubule network as a promising strategy to enhance efficacy of CTL-based immunotherapy against solid tumors, especially stiff solid tumors.